2004
DOI: 10.1007/s00147-004-0733-4
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of cyclosporine exposure in heart, kidney or liver transplant recipients on maintenance therapy

Abstract: We investigated the relationship between cyclosporine exposure and the presence of cyclosporine-related side effects and assessed the advantage of the cyclosporine concentration 2 h postdose (C,) over pre-dose concentration (C,) monitoring. Cyclosporine area-under-the-concentration-time curves were measured during the absorption phase (AUCw h) in 49 liver, 28 heart and 26 kidney transplant recipients (time since transplantation > 6 years) with or without cyclosporine-related side effects on maintenance therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…According to Cantarovich et al (20), these trough levels result in C2‐levels of about 1000 ng/mL. Moreover, Hesselink et al (21) showed that Cmax levels of CsA in LTX‐recipients are about 200 ng/mL higher than C2‐levels. Consequently, it is conceivable that during the first month after transplantation, CsA peak levels of about 1200 ng/mL may have been reached in our study cohort.…”
Section: Resultsmentioning
confidence: 99%
“…According to Cantarovich et al (20), these trough levels result in C2‐levels of about 1000 ng/mL. Moreover, Hesselink et al (21) showed that Cmax levels of CsA in LTX‐recipients are about 200 ng/mL higher than C2‐levels. Consequently, it is conceivable that during the first month after transplantation, CsA peak levels of about 1200 ng/mL may have been reached in our study cohort.…”
Section: Resultsmentioning
confidence: 99%
“…The AUC from 0 to 4 h (AUC 0‐4 ) was 0.62 μg • h/mL. This result was also significantly lower than the target AUC 0‐4 for this patient (a recommended C 2 of 600 ng/mL corresponds to an AUC 0‐4 of around 1.9 μg • h/mL) . This low AUC was explained by the unexpected low C 2 observed in this patient (191 ng/mL).…”
Section: Case Reportmentioning
confidence: 57%